2015
DOI: 10.1016/j.neuroscience.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The long-lasting antidepressant effects of rapastinel (GLYX-13) are associated with a metaplasticity process in the medial prefrontal cortex and hippocampus

Abstract: Rapastinel (GLYX-13) is an N-methyl-D-aspartate receptor (NMDAR) modulator that has characteristics of a glycine site partial agonist. Rapastinel is a robust cognitive enhancer and facilitates hippocampal long-term potentiation (LTP) of synaptic transmission in slices. In human clinical trials, rapastinel has been shown to produce marked antidepressant properties that last for at least one week following a single dose. The long-lasting antidepressant effect of a single dose of rapastinel (3 mg/kg IV) was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 43 publications
2
61
0
3
Order By: Relevance
“…A recent report demonstrates that GLYX-13 also causes a rapid increase in the number of spine synapses in the PFC (Burgdorf et al, 2015a). The ability of rapid-acting antidepressants to cause fast release of BDNF in primary neuronal cultures is consistent with the possibility that these agents stimulate dendrite complexity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report demonstrates that GLYX-13 also causes a rapid increase in the number of spine synapses in the PFC (Burgdorf et al, 2015a). The ability of rapid-acting antidepressants to cause fast release of BDNF in primary neuronal cultures is consistent with the possibility that these agents stimulate dendrite complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, GLYX-13 reverses chronic stress-induced reduction in NMDAR-dependent LTP [217], which is a mechanism hypothesized to mediate its antidepressant actions. Moreover, similar to ketamine, GLYX-13 enhances hippocampal LTP in brain slices taken 24 h and 7 days following a single in vivo injection in rodents [218]. …”
Section: Mechanisms Underlying Fast/rapid Onset Antidepressants Acmentioning
confidence: 99%
“…However, the antidepressant actions of both GLYX-13 and ketamine are blocked by pretreatment with an AMPA receptor antagonist, indicating a requirement for glutamate-AMPA receptor activity (Burgdorf et al, 2013;Li et al, 2010;Maeng et al, 2008) 4 We have previously demonstrated that ketamine increases synaptic number and function in the mPFC, and shown that these effects depend on mTORC1 signaling (Li et al, 2010;Li et al, 2011). GLYX-13 is reported to enhance neuroplasticity suggesting that it may also enhance synaptic function (Burgdorf et al, 2015a(Burgdorf et al, , 2015b). In the current study, we compared the influence of GLYX-13 and ketamine on the mTORC1-signaling pathway and on the number and function of spine synapses in the rat mPFC.…”
Section: Introductionmentioning
confidence: 99%